Community Service Program: Socialization and Introduction of “DAGUSIBU” to Santri at BTRG Islamic Boarding School, Aceh: Pengabdian Kepada Masyarakat: Sosialisasi dan Pengenalan “DAGUSIBU” pada Santri Dayah BTRG Aceh - Ida Mukhlisa; Rosa Mardiana; Lidyawati; Nurjannah; Dwi Putri Rejeki; Sasmiati Farach Dita; Novita, Eva (Jurnal Mitra Pengabdian Farmasi, 2025)
Irrational use of medicines remains a public health problem, including among adolescents in religious educational institutions. Santri living in Islamic boarding schools are required to be independent in managing their daily health needs, which may increase the risk of improper medicine use if adequate knowledge is lacking. This community service activity aimed to improve the knowledge and understanding of santri at BTRG Islamic Boarding School, Aceh, regarding proper medicine management through the socialization and introduction of the DAGUSIBU concept (Get, Use, Store, and Dispose of Medicines Properly). The activity was conducted using an educational and participatory approach, including lectures, interactive discussions, and the distribution of educational media. A total of 52 santri participated in the activity, consisting of 30 male and 22 female santri. The results showed an improvement in santri’s understanding of DAGUSIBU principles, as indicated by active participation during the sessions and their ability to explain the material after the activity. This program had a positive impact on increasing awareness of rational medicine use among santri. Therefore, continuous DAGUSIBU education is recommended to enhance health literacy in Islamic boarding school environments.